ANALISIS CONTAGION EFFECT RESESI GLOBAL KE INDEKS PASAR MODAL ASEAN - Ana Elisa; Satria, Dias (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Covid-19 pandemic, the Russia-Ukraine war, and the increase in inflation in the United States have triggered a recession, leading to corrections in the global stock markets, including the ASEAN stock index. This research aims to examine how the relationships between stock markets in the ASEAN region mutually influence each other and seeks to identify which stock index exerts a dominant influence. This study employs the Vector Error Correction Mechanism (VECM) method, utilizing daily closing data from the stock indices of the Philippines (PSEi), Malaysia (KLCI), Indonesia (IHSG), Thailand (SET), and Singapore (STI) from 2018 to 2022. The findings indicate that in the short term, only STI influences PSEi, but in the long term, it is influenced by KLCI, IHSG, and STI. In the short term, KLCI is affected by PSEi, SET, and STI, while in the long term, it is influenced by PSEi, IHSG, and STI. In the short term, IHSG is impacted by PSEi, SET, and STI, while in the long term, it is influenced by PSEi, KLCI, and STI. In the short term, SET is influenced by PSEi and STI, while in the long term, it is influenced by PSEi, KLCI, IHSG, and STI. In the short term, PSEi, KLCI, IHSG, and SET do not influence STI, but in the long term, they are influenced by PSEi, KLCI, and IHSG. These five ASEAN stock indices are predominantly influenced by their respective stock indices.